1996
DOI: 10.1021/bi9527202
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase β:  Pre-Steady-State Kinetic Analysis and Roles of Arginine-283 in Catalysis and Fidelity

Abstract: DNA polymerase beta (pol beta) is the smallest and least complex DNA polymerase. The structure of the enzyme is well understood, but little is known about its catalytic properties, particularly processivity and fidelity. Pre-steady-state analysis of the incorporation of a single nucleotide into a short 25/45 oligonucleotide primer-template by pol beta was used to define the kinetic parameters of the polymerase. In addition, nucleotide analogs and site-specific mutants, along with structural analyses, were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
182
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(210 citation statements)
references
References 45 publications
26
182
2
Order By: Relevance
“…4) suggest that the rate-limiting step is associated with TS 3, namely the partial rotation of Arg-258 (overall barrier of 20.5 Ϯ 3 k B T). This value is lower but comparable to the overall rate of the reaction (25-28 k B T), as obtained from experimental kinetic data [k pol , the overall rate of nucleotide incorporation of 3-90 s Ϫ1 (27)(28)(29)(30)(31)(32)(33)]. This rate-limiting conformational barrier in the same order of the overall (conformational and chemical steps) reaction profile immediately suggests site-specific mutant experiments on Arg-258 to assess Arg-258's effect on reaction efficiency and fidelity.…”
Section: Discussion: Rate-limiting Steps and Implications For Polymersupporting
confidence: 79%
See 1 more Smart Citation
“…4) suggest that the rate-limiting step is associated with TS 3, namely the partial rotation of Arg-258 (overall barrier of 20.5 Ϯ 3 k B T). This value is lower but comparable to the overall rate of the reaction (25-28 k B T), as obtained from experimental kinetic data [k pol , the overall rate of nucleotide incorporation of 3-90 s Ϫ1 (27)(28)(29)(30)(31)(32)(33)]. This rate-limiting conformational barrier in the same order of the overall (conformational and chemical steps) reaction profile immediately suggests site-specific mutant experiments on Arg-258 to assess Arg-258's effect on reaction efficiency and fidelity.…”
Section: Discussion: Rate-limiting Steps and Implications For Polymersupporting
confidence: 79%
“…1), pol ␤ fills single-stranded gaps in DNA with relatively high accuracy (fidelity): it recruits the nucleotide unit (dNTP, 2Ј-deoxyribonucleoside 5Ј-triphosphate) complementary to the template base (e.g., C opposite G) about 1,000 times more often than the incorrect unit (e.g., T opposite G) (27)(28)(29)(30)(31)(32)(33). Closed and open conformations of pol ␤ have been solved by x-ray crystallography by Wilson and coworkers (19,34) and are related by a large subdomain motion (Ϸ6 Å) of the thumb (Fig.…”
mentioning
confidence: 99%
“…This side chain is hydrogen-bonded to the sugar of the preceding template nucleotide in the template⅐primer duplex. Previous studies have shown that the R283A mutant of pol ␤ has greatly reduced fidelity consistent with the importance of these interactions for polymerase selectivity (16,21,22). This phenotype includes an error rate of 25% for T⅐dGMP (16), suggesting complete loss of discrimination.…”
supporting
confidence: 58%
“…Amino acid residues important for catalysis and fidelity, including Arg-283, Met-282, and Phe-272, are not poised for catalysis in the open conformation of the enzyme. However, once the enzyme assumes the closed conformation, these residues are brought into proper geometry for catalysis and for monitoring the fidelity of the chemical step (29,43). Residues Arg-283 and Phe-272 form hydrogen bonds and van der Waals contacts with the templating nucleotide in the closed conformation.…”
Section: T79s Commits 1-base Insertion Mutations-mentioning
confidence: 99%